E-Filing and Tax Revenue: a Role of Digital Tax Socialization - Dendy Syaiful Akbar; Rifki Abdul Malik; Benny Prawiranegara; Ali Muhidin; Linda Melinda Tijani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to analyze the effect of the use of e-filing on the tax revenue by including the role of digital tax socialization to strengthen both relationships. The new contribution of this study is to combine literature e-filing, digital tax socialization, and tax revenue previously examined separately. For analysis, we use Moderated Regression Analysis (MRA) which was built through cross-sectional data for 7 years on the tax authorities in the regions. The study results show that e-filing has a positive effect on tax revenue. Subsequent results provide evidence that digital tax socialization can strengthen the positive effect of e-filing on tax revenue. In this study, we found that digital tax socialization directly has a negative relationship with tax revenue. The results of our study support the commitment of various countries to carry out tax reforms in a modern direction.